HR-Commitment and Digital Organizational Communication To Improve the Digital-Quality Services in Private Universities - Iwan Ardiansyah; taufiq rahmat; Masluh Masluh; Heri Heri; Diah Apriliani (Khazanah Sosial, 2023)
The main issue in this research is the weak Quality of private universities in utilizing digital media in the industrial era 4.0, which leads to the formation of professionalism in the form of an innovative campus, which according to researchers, is influenced by organizational Commitment and digital organizational communication. Target group private universities in Bandung. This study's descriptive survey research design is based on a verification methodology. Data was collected through survey techniques by distributing questionnaires to as many as 69 respondents, all employees. Analysis in data processing using path analysis. It is based on the findings of the verification analysis, with r2 = 0.587, or 58.7%, as the coefficient of determination. The results show that the Quality of digital services is influenced by organizational Commitment and digital communication, both simultaneously and simultaneously. In comparison, there is still the influence of other external factors, which has not been studied, and is 41.3% academically recognized. Research findings also reveal that optimizing digital services can be done by first improving the Commitment of human resources to utilizing digital media in communication.